Pendekatan Persepsi dan Pengambilan Keputusan Individual oleh Kiai di Pondok Pesantren dalam Perspektif Stephen P. Robbins - Andriyani, Ida; Kurniawan, Muhammad Rafiq; Agustina, Ike Yama (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
The purpose of this study is to find out how decisions should be made in Islamic boarding schools, and what a kiai can do to improve their decision making by adopting a perception approach. This study uses a qualitative approach to the type of research literature review (library research). The primary data sources that will be used are the theories and concepts proposed by Stephen P. Robbins in his book Organizational Behavior. Data analysis will be carried out in three stages, namely; 1. Deductive; 2. Interpretive; and, 3. Comparative. After conducting a literature study or literature review, it can be concluded that there are five steps that the kiai can take in making decisions, namely; (1) analyze the situation; (2) understand bias; (3) combining rational analysis with intuition; (4) selecting the relevant decision-making style for the specific case; and (5) increase creativity.